The biology of Boopsoidea inornata (Castelnau, 1861) and life history comparisons within the Sparidae - Ensair, Hend Assiad M (Department of Biological Sciences, 2020)
South African marine ichthyofauna has remarkable diversity across a range of biogeographic zones from cold-temperate to subtropical. Two families stand out here, both with high diversity and high rates of endemism to the region, namely Sparidae and Clinidae. The Sparidae are of greater interest because of their commercial importance, and conversely, their conservation status. Several are listed as threatened by the IUCN. The Sparidae is also the family with the greatest plasticity in life history characteristics of any vertebrate family, as they include gonochorism, rudimentary hermaphrodites, and both kinds of sequential hermaphrodites. Life history characteristics are known determinants of the resilience of fish species to fishing, and more generally of their response, either positive or negative, to any form of disturbance. Life history characteristics of most of the species of Sparidae, in South Africa and worldwide, have been studied, particularly those of commercial and conservation importance. Omissions include those that are small, with little commercial importance. This is an oversight, as there is much to be learned about life history strategies by studying the full spectrum of variation in the family, and particularly those variants which produce numerically, and therefore ecologically, significant population sizes. In this thesis, I study the life history and parasite community of one of South Africa’s most abundant seabreams in separate chapters. In the last chapter I take a fresh perspective on life history variation among fishes, by comparing four sympatric seabreams to describe the several dimensions along which life history trade-offs can occur without the confounding influences of environment and phylogeny. Boopsoidea inornata (Castelnau, 1861) is endemic to South Africa. Eight hundred and seventeen fishes were sampled from four locations: False Bay, Struisbaai, Goukamma and Port Elizabeth from 2012 to 2014. They ranged in size from 130 to 310 mm fork length. The diet of B. inornata was investigated in False Bay and Struisbaai using Prey-Specific Index of Relative Importance (%PSIRI). B. inornata is an omnivore, with a preference towards small sand- and reef-dwelling prey and has only limited intake of algae and small fish. Age and growth were assessed using sectioned otoliths. A clear seasonal pattern of band formations deduced from the frequency of opaque margins show that B. inornata lay down one opaque and one transparent band per year. B. inornata is a small species (L∞= 222.7 mm) with high longevity (tmax= 37). It is a rudimentary hermaphrodite. The ovaries hold up to 8000 vitellogenic eggs, which equates to an average 19 eggs per gram of body mass. This value is low compared with other seabream species. B. inornata females spawn repeatedly during the year, although there is more spawning activity in spring, than in other months. The sex ratio is heavily skewed towards females (1:3.35). The presence of post-ovulatory follicles together with hydrated oocytes indicates that the species is an indeterminate batch spawner. Length at 50% maturity was calculated based on gonads collected throughout the spawning season. Females mature at 178 mm FL, compared to 185 mm FL for males. Female GSI greatly exceeds male GSI, and, together with the sex ratio, suggests a polygamous mating system. One hundred and fifty B. inornata were collected from False Bay, Struisbaai, Goukamma and Port Elizabeth to investigate associated parasite assemblages. Eighty six percent of the sample was infected by parasites. Parasites infecting B. inornata have never before been recorded. Nineteen parasite taxa were found infecting B. inornata across all localities and included myxozoan, monogenean, digenean, cestode, nematode, copepod and isopod representatives. Three species of digenean metacercaria showed high prevalence of infection in B. inornata across all four localities. These included a Stephanostomum sp. infecting the gill arches of 61%, and two unidentified digeneans. The unidentified digenean metacercariae- 2 was found in the kidneys and musculature of 59% of the total sample and the unidentified digenean metacercariae-1 was found infecting the hearts of 47% of the total sample. Overall parasite assemblages were significantly different amongst all localities, with no significant difference in parasite assemblages among size classes, age classes or sex within localities. Fish life history is affected by environmental and biological factors but is also constrained by phylogenetic influences on morphology and physiology. In an attempt to expose the nature and extent of life history trade-offs, I compared four closely related and sympatric seabreams, namely Spondyliosoma emarginatum, Pachymetopon blochii, Rhabdosargus globiceps and Boopsoidea inornata. I contend that only by eliminating or reducing as far as possible the effect of environment, habitat and phylogeny can we expose real trade-offs. Samples of each species were obtained in every season from the south-western Cape, South Africa, to obtain measures of total length, mass, gonadosomatic index and condition. S. emarginatum is a nest-guarding, short-lived, protogynous hermaphrodite. P. blochii is a resident, group-spawner, engaging in sperm competition. R. globiceps is a moderately long-lived migrant with a sex ratio of 1:1, that also engages in sperm competition over a short spawning season. B. inornata is a polygamous, long-lived resident with low annual fecundity, but a protracted spawning season. Although all four species are periodic strategists, life history trade-offs exist between several sets of variables, namely semelparity vs iteroparity, age-at-maturity vs maximum size, annual fecundity vs longevity, length of spawning season vs parental care, and length of spawning season vs migration. The efficiency of the sequential hermaphrodite strategy which allows every fish to spawn as a female until they are large enough to act as a male makes one question the rarity of this strategy. I argue that halving of the female life-span compromises the periodic strategy, and that hermaphroditism is at odds with migration. The latter rests on the assumption that the migrant social structure is based on cooperation, for feeding, defence and navigating in schools, whereas the hermaphrodite social structure is based on aggression and dominance hierarchies which requires residency and territoriality. No clear adaptive reason for the divergence among the sympatric species can be identified, although competition among the young is a candidate. This comparison reveals a wide range of options available to seabreams and shows how disparate life histories can be equally adaptive under identical conditions. More generally I have shown how a variety of life-history traits, such as migration, sex-ratio, reproductive strategy and somatic growth form interact to define a life-history.